Daily sedation interruption and mechanical ventilation weaning: a literature review - Vagionas, Dimitrios; Vasileiadis, Ioannis; Rovina, Nikoletta; Alevrakis, Emmanouil; Koutsoukou, Antonia; Koulouris, Nikolaos (Anestezjologia Intensywna Terapia, 2019)
Daily sedation interruption (DSI) is a method used since the beginning of the millennium to streamline sedation in critically ill patients under mechanical ventilation and improve clinical outcomes. The purpose was to assess whether there is a correlation between DSI and weaning from mechanical ventilation. We designed a literature review via searching PubMed, UpToDate and Google Scholar for relevant key terms from inception until March 2019. Literature retrieved included nine randomized controlled trials. When compared to usual practice, it is superior in terms of duration of mechanical ventilation, stay in the intensive care unit, hospitalization, adverse effect occurrence and total cost of therapy. Comparison with other sedation protocols produces conflicting results. DSI, and protocolized sedation in general, are safe methods to perform to facilitate earlier weaning and improved clinical outcomes. Future research should focus on minimizing bias by conducting double-blinded studies and studying different patient subgroups.